Efektivitas Peraturan Daerah Kabupaten Gresik Nomor 7 Tahun 2021 Tentang Desa Wisata - M. Akbar Firmansyah Putra; Lukman Arif (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Tourism village-based tourism is one of the regional development strategies that is oriented towards community empowerment, improving the local economy, and preserving the environment in a sustainable manner. Gresik Regency implements this policy through Regional Regulation Number 7 of 2021 concerning Tourism Villages, one of which is the development of the Banyuurip Mangrove Center (BMC) in Ujungpangkah District as an ecotourism destination based on mangrove conservation. This study aims to analyze the effectiveness of the implementation of Gresik Regency Regional Regulation Number 7 of 2021 concerning Tourism Villages in the development of the Banyuurip Mangrove Center (BMC) Tourism Village in Ujungpangkah District, Gresik Regency. The research uses a qualitative approach with a case study method. Data collection was carried out through in-depth interviews, observations, and documentation. The research informants consisted of officials from the Gresik Regency Tourism Office, the Banyuurip Village Government, BMC managers, local communities, and tourism business actors. Data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawn, while data validity is tested through triangulation of sources, techniques, and time. The results of the study show that the implementation of Gresik Regency Regional Regulation Number 7 of 2021 concerning Tourism Villages in the development of the Banyuurip Mangrove Center (BMC) is quite effective. The findings of the study show that: (1) the achievement of policy objectives has been seen through the development of mangrove conservation-based tourism that provides economic, social, and environmental benefits for the community; (2) the alignment between planning and implementation is running quite well through the implementation of mangrove rehabilitation programs, educational tourism, and the construction of tourist facilities, although there are still constraints on funding and human resource capacity; (3) the institutional capacity of tourism managers has been formed and is able to carry out management functions, but still requires strengthening competence, professionalism, and resource support; (4) the quality of governance shows the application of the principles of transparency, participation, and accountability in tourism management, although the effectiveness of program evaluation still needs to be improved; (5) collaboration between actors has involved the government, communities, academics, and the private sector in the development of tourism and mangrove conservation, but coordination and synergy between stakeholders have not been fully optimal; and (6) the resulting sustainable impacts include increasing community economic activities, growing environmental awareness, and maintaining the mangrove ecosystem as a conservation area. However, challenges in the form of limited resources, funding, and institutional strengthening still need attention to increase policy effectiveness in a sustainable manner.